PENDIOIKAN SEJARAH DAN NASIONALISME - Kumalasari, Dyah (Jurnal Cakrawala Pendidikan, 2016)
This article aims at reviewing how far history instruction has been able to build nationalism spirit among the learners. Diversities of Indonesian people as an objective condition, especially in terms of ethnics, religions, cultures, and languages have been very susceptible to and potential causes of disintegration of Indonesian people..History education laden with values of the· national struggles .for independence is considered as strategic media for rebuilding the nationalism spirit among the learners. Reinventing nationalism spirit among the learners ·as representatives for youth generation is very crucial for maintaining Indonesian integrity as an integrated nation.